Zwischen Bildungsmisere und Bildungsreform(en): Reflexionen angehender Fremdsprachenlehrkräfte über moderne Bildungssysteme und Zukunftsperspektiven des institutionellen Fremdsprachenlernens - Durbaba, Olivera (Neofilolog, 2023)
This paper presents a small-scale empirical study which included 21 senior-year students of German as a major who took a course on the methodology of teaching German as a foreign language in the spring semesters 2020 and 2021, at the Faculty of Philology at the University of Belgrade (Serbia). The students were encouraged to read several articles by the Austrian educational philosopher Konrad Paul Liessmann and to record their reflections on the possible effects of the commercialization of purpose-oriented knowledge. The articles in question are based on Liessmann’s so-called “Theory of Uneducation”. The students’ tasks were analyzed and discussed, with the focus on their statements regarding the following aspects: a) possible challenges, opportunities and dangers of unavoidable digitization and mechanization in everyday life and at school, and b) the changing roles and tasks in the educational context. All this more or less aims at application-oriented knowledge management. The participants supported Liessmann’s thesis that education is losing value through commercial exploitation, accumulation of TV quiz knowledge and extensive testing and examining. However, his skepticism with regard to digitization in the school system and his plea for more traditional canons of school subjects were mostly met with disapproval by the participants.